PENGARUH PENGGUNAAN MEDIA SOSIAL DAN KUALITAS PELAYANAN TERHADAP MINAT PEMBELIAN ULANG PADA UMKM DI SURAKARTA DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI - Vio Ardana Listyandita Putra; Irmawati (Program Studi Manajemen | Universitas Pasir Pengaraian, 2024)
The purpose of this study was to analyze the effect of social media use and service quality on repurchase interest in UMKM in Surakarta with customer satisfaction as a mediating variable. This research method uses a quantitative approach. The population in this study are consumers who have shopped at MSMEs in Surakarta. The sample used in this study were 105 respondents. The results of this study are Social Media has a negative and significant effect on Repurchase Interest. Service Quality has a positive and significant influence on Repurchase Interest. Social Media has a positive and significant influence on Customer Satisfaction. Service quality has a positive and significant influence on customer satisfaction. Customer Satisfaction has a positive and significant influence on Repurchase Interest. Social Media has a positive and significant influence on Repurchase Interest through Customer Satisfaction.